2013
DOI: 10.1371/journal.pone.0081177
|View full text |Cite
|
Sign up to set email alerts
|

Activity in a Premotor Cortical Nucleus of Zebra Finches Is Locally Organized and Exhibits Auditory Selectivity in Neurons but Not in Glia

Abstract: Motor functions are often guided by sensory experience, most convincingly illustrated by complex learned behaviors. Key to sensory guidance in motor areas may be the structural and functional organization of sensory inputs and their evoked responses. We study sensory responses in large populations of neurons and neuron-assistive cells in the songbird motor area HVC, an auditory-vocal brain area involved in sensory learning and in adult song production. HVC spike responses to auditory stimulation display remark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Recent experiments have used 2-photon imaging of HVC activity in the anesthetized zebra finch to measure sensory responses within that structure (Graber et al, 2013; Peh et al, 2015). In order to adapt this approach to address motor dynamics, we developed a head-fixed singing bird preparation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experiments have used 2-photon imaging of HVC activity in the anesthetized zebra finch to measure sensory responses within that structure (Graber et al, 2013; Peh et al, 2015). In order to adapt this approach to address motor dynamics, we developed a head-fixed singing bird preparation.…”
Section: Resultsmentioning
confidence: 99%
“…These nonuniformities may arise from a number of sources. For instance, because our recordings were spatially restricted within HVC, a sampling bias may exist if burst events from nearby cells exhibit similar timing (Graber et al, 2013; Markowitz et al, 2015; Peh et al, 2015). We next tested whether any nonuniformities could be explained by the coincident activity of neurons with motor movements.…”
Section: Discussionmentioning
confidence: 99%
“…In anesthetized and spontaneously sleeping male finches, neurons in nuclei of the forebrain song system exhibit spontaneous bursts of activity [46,47]. Bursts in one nuclei often precede bursts in another distantly located nuclei, raising the possibility that this sequential activity is involved in processing song-related information [48,49].…”
Section: Resultsmentioning
confidence: 99%
“…Graber et al have shown that the elevation in Ca 2+ concentration in astrocytes is induced by auditory stimulation in the HVC, a cortical motor area (Graber et al, ). The function of HVC astrocytic sensory responses is unknown.…”
Section: Sensory Responses In Host Astrocytesmentioning
confidence: 99%